Caboca - Skarheim, Mariara da Rocha (Australia, 2011)
For the last decade filmmaker Maiara da Rocha Skarheim has embraced Australia as home. But recently she had a calling; an urge to return to her birthplace Brazil and explore the notion of what life would have been like if she had never left. Thus Maiara returns to the land of her childhood in an attempt to reconnect with the places and people she left behind all those years ago. Here, she searches for a sense of identity, a connection with the country, and a rekindling of family-ties while coming to terms with the inevitability of change – both in herself and her motherland.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films